2008
DOI: 10.1088/0957-4484/19/04/045711
|View full text |Cite
|
Sign up to set email alerts
|

Electrical transport studies of individual IrO2nanorods and their nanorod contacts

Abstract: We have studied the electrical transport properties of individual single-crystalline IrO(2) nanorods prepared by the metal-organic chemical vapour deposition method. With the help of the standard electron-beam lithographic technique, individual nanorods are contacted by Cr/Au submicron electrodes from above. Utilizing two-probe, three-probe and four-probe measurement configurations, not only the intrinsic electrical transport properties of the individual nanorods but also the electronic contact resistances, R(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 47 publications
4
29
0
Order By: Relevance
“…Our fitted values of βnormalint106−1 0−5 K −2 are in similar orders of magnitude with those previously obtained in normal metals, such as Au [8], Al [9], and AuPd [11]. What is more interesting is that previous studies of a variety of metals have found that the EPI interference effect was important only at considerably low temperatures [8-12]. In sharp contrast, we find that in our TiSi NWs, ρ int ( T ) can largely dominate over ρ BG ( T ) even up to temperatures as high as room temperature.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Our fitted values of βnormalint106−1 0−5 K −2 are in similar orders of magnitude with those previously obtained in normal metals, such as Au [8], Al [9], and AuPd [11]. What is more interesting is that previous studies of a variety of metals have found that the EPI interference effect was important only at considerably low temperatures [8-12]. In sharp contrast, we find that in our TiSi NWs, ρ int ( T ) can largely dominate over ρ BG ( T ) even up to temperatures as high as room temperature.…”
Section: Resultssupporting
confidence: 88%
“…This unique property renders the TiSi NWs useful for the investigations of the interplay among a variety of electron-scattering processes at the nanoscale level. Previously, the EPI interference effect has been found to be important in normal metals only at considerably lower temperatures [8-12]. …”
Section: Introductionmentioning
confidence: 99%
“…The morphology and atomic structure of the nanowires were studied by scanning electron microscopy (SEM) and transmission electron microscopy. Four-probe single nanowire devices were fabricated by the electron-beam lithography, as described previously [22]. (The inset of Figure 1 shows an SEM image of the NW1 device taken from [22].…”
Section: Methodsmentioning
confidence: 99%
“…Four-probe single nanowire devices were fabricated by the electron-beam lithography, as described previously [22]. (The inset of Figure 1 shows an SEM image of the NW1 device taken from [22]. In [22], the electrical transport properties of the two NW1 and NW2 nanowire devices had been studied at high temperatures of 30 to 300 K.) The resistance measurements were performed on a standard 4 He cryostat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation